Genotype/phenotype correlations in 538 congenital adrenal hyperplasia patients from Germany and Austria: discordances in milder genotypes and in screened versus prescreening patients - Riedl, Stefan; Röhl, Friedrich-Wilhelm; Bonfig, Walter; Brämswig, Jürgen; Richter-Unruh, Annette; Fricke-Otto, Susanne; Bettendorf, Markus; Riepe, Felix Günther; Kriegshäuser, Gernot; Schönau, Eckhard; Even, Gertrud; Hauffa, Berthold; et al. (Endocrine Connections, 2019)
Congenital adrenal hyperplasia (CAH) due to CYP21A2 gene mutations is associated with a variety of clinical phenotypes (salt wasting, SW; simple virilizing, SV; nonclassical, NC) depending on residual 21-hydroxylase activity. Phenotypes and genotypes correlate well in 80–90% of cases. We set out to test the predictive value of CAH phenotype assignment based on genotype classification in a large multicenter cohort. A retrospective evaluation of genetic data from 538 CAH patients (195 screened) collected from 28 tertiary centers as part of a German quality control program was performed. Genotypes were classified according to residual 21-hydroxylase activity (null, A, B, C) and assigned clinical phenotypes correlated with predicted phenotypes, including analysis of Prader stages. Ultimately, concordance of genotypes with clinical phenotypes was compared in patients diagnosed before or after the introduction of nationwide CAH-newborn screening. Severe genotypes (null and A) correlated well with the expected phenotype (SW in 97 and 91%, respectively), whereas less severe genotypes (B and C) correlated poorly (SV in 45% and NC in 57%, respectively). This was underlined by a high degree of virilization in girls with C genotypes (Prader stage >1 in 28%). SW was diagnosed in 90% of screening-positive babies with classical CAH compared with 74% of prescreening patients. In our CAH series, assigned phenotypes were more severe than expected in milder genotypes and in screened vs prescreening patients. Diagnostic discrimination between phenotypes based on genotypes may prove overcome due to the overlap in their clinical presentations.
Gesehen am 11.07.2019